ANALISIS INTEGRATIF PERSPEKTIF AL-QUR'AN DAN SAINS PENDIDIKAN MODERN - Annisa Amalia Puspita Dewi; Fasya Amrina Rosyada; Ana Nur Khikmah (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2026)
This study aims to analyse the educational values embodied by Luqman in the Qur'an and examine their relevance to the dynamics of modern education through the integration of Qur'anic teachings and contemporary educational science. The research employed a qualitative library research method using an integrative approach. Primary data were obtained from the Qur'an, particularly Surah Luqman verses 12–19, supported by classical and contemporary Qur'anic commentaries, while secondary data were collected from books and scientific journals related to Islamic education and modern educational theories. Data was analysed using content analysis by identifying educational values, interpreting Qur'anic exegesis, and integrating the findings with contemporary educational concepts. The findings reveal that Luqman's educational model emphasizes the values of monotheism (tawhid), gratitude, moral awareness, worship, noble character, and social responsibility. These values are consistent with modern educational theories, including character education, positive psychology, social learning theory, constructivism, and educational neuroscience. The study concludes that Luqman's educational concept represents a holistic educational model that integrates spiritual, intellectual, emotional, and social dimensions. Therefore, it can serve as a relevant paradigm for strengthening Islamic education in addressing the challenges of the digital era and contemporary educational transformation.